Empowering Early Childhood Educators: Innovative Approaches to Literacy Instruction - Nila Fitria (Early Childhood Development Gazette, 2024)
This study aims to describe the smart teaching of kindergarten teachers in teaching literacy. Smart teaching literacy is the ability of teachers to teach literacy. The problems found in literacy teaching are related to the ability to recognize the alphabet, write the alphabet, and read.  This research is qualitative research using observation and in-depth interviews and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of this study show that smart teaching carried out by kindergarten teachers in teaching literacy as a means of exploration, experimentation, and self-expression for children uses various types of media used in smart teaching, including digital media, namely through the Kids Academy application. Smart teaching literacy is expected to have open and effective communication, involve parents, create a positive environment, and provide rewards and consequences to children.